Naphthaleneacetc acid associate to potassium fertilization on coffee sprouting conilon - Força Baroni, Danilo; Silva dos Reis, Luciléa; Corona Baitelle, Diego; Moraes Vieira, Kezia; Celestino Meireles, Robson; Verdin Filho, Abraão Carlos; Ramalho Haddade, Ismail (Coffee Science - ISSN 1984-3909, 2017)
Spending on labor may represent more than 50% of the total production cost of Conilon coffee, and pruning and thinning responsible for most of these costs, behind only the harvest expenses. Some growth phytoregulator auxin group associated with potassium (K2O) can reduce bud emission. It is aimed to work verify the effect of naphthalene acetic acid (NAA) associated with potassium fertilization on budding Conilon coffee. The experiment was carried out from June 2014 to December 2015 in adult crop of non-irrigated Conilon coffee, the cultivate “G35-Verdebrás” located at the Federal Institute of the Holy Spirit - Campus Santa Teresa. The randomized blocks were used with the 5x4 factorial arrangement between levels of NAA and levels of K2O, respectively. They were applied five doses of NAA (0, 50, 100, 250 and 500 mg L-1) and four of K2O in the fertilizer (60, 120, 240 and 480 kg ha-1). It was observed that the application of NAA influences the emission of shoots for favoring apical dominance of the plants. K2O levels applied interfere with the action of NAA, and the application of high doses of nutrient can inhibit the action of this phytoregulator. The application of 344 mg L-1 NAA associated with fertilization of 120 kg ha-1 of K2O, reduced the number of shoots per plant without interfering with the productivity and development of the remaining shoots.